Application of Xanthan-Gum-Based Edible Coating Incorporated with Litsea cubeba Essential Oil Nanoliposomes in Salmon Preservation - Haiying Cui; Mei Yang; Ce Shi; Changzhu Li; Lin Lin (Foods, 2022)
Salmon is prone to be contaminated by Vibrio parahaemolyticus (V. parahaemolyticus), leading to the deterioration of salmon quality and the occurrence of food-borne diseases. In this study, we aimed to develop a novel xanthan-gum-based edible coating embedded with nano-encapsulated Litsea cubeba essential oil (LC-EO) for salmon preservation at 4 °C. First, the results of the growth curves and scanning electron microscopy (SEM) showed that LC-EO displayed potent antibacterial activity against V. parahaemolyticus; the optimal concentration of LC-EO in the liposomes was 5 mg/mL, and the maximal encapsulation efficiency (EE) was 37.8%. The particle size, polydispersity coefficient (PDI), and zeta potential of the liposomes were 168.10 nm, 0.250, and −32.14 mV, respectively. The rheological test results of xanthan-gum-based edible coatings incorporating liposomes showed that the prepared coating was suitable for applying on food surfaces. The results in the challenge test at 4 °C demonstrated that the treatment of 1:3 (liposome: xanthan gum, v/v) coating performed the best preservative properties, the coating treatment delayed the oxidation of salmon, and controlled the growth of V. parahaemolyticus. These findings suggest that the coatings formulated in this study could be used as a promising approach to control V. parahaemolyticus contamination and maintain salmon quality.